Melon Waste Ecoenzyme: An Eco-friendly Liquid Organic Fertilizer for Vegetative Growth of Melon (Cucumis melo L. var. Merlin) - Ulmillah, Aulia; Satitiningrum, Yuni; Agilliana, Intan (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
The utilization of melon plant waste, such as fruit peels, leaves, and stems, can be done by processing it into eco-enzyme, which is then used as liquid organic fertilizer. This study aims to assess the effect of eco-enzyme on the vegetative growth of melon plants. The randomized block design (RBD) method was used with seven treatments and four replications, including P0 (negative control), P1 (10 mL/L), P2 (20 mL/L), P3 (30 mL/L), P4 (40 mL/L), P5 (50 mL/L), and P6 (positive control). Observations were made every 7 days for 30 days, with parameters including plant height, leaf area, number of leaves, plant fresh weight, and root fresh weight. Data analysis was conducted using one-way ANOVA and Duncan’s test. The results showed that treatment P5 (50 mL/L) produced the best results with a plant height of 36.68 cm, leaf area of 137.33 cm², 11.56 leaves, plant fresh weight of 67.1 g, and root fresh weight of 2.24 g. These results were not significantly different from the positive control (P6). Thus, eco-enzyme had a significant effect on the vegetative growth of melon plants.